2023
DOI: 10.1210/jendso/bvad037
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Clinical Trial of Intranasal Oxytocin to Promote Weight Loss in Individuals With Hypothalamic Obesity

Abstract: Context Hypothalamic obesity is a rare, treatment-resistant form of obesity. In preliminary studies, the hypothalamic hormone oxytocin (OXT) has shown promise as a potential weight loss therapy. Objective To determine whether 8 weeks of intranasal OXT (vs. 8 weeks of placebo) promotes weight loss in children, adolescents, and young adults with hypothalamic obesity. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…These positive results could be attributable to the numerous metabolic effects of the neurohormone, including direct reduction of food intake by decreasing appetite in homeostatic and reward-driven conditions (hence, properly insisting on hypothalamic regions involved in the regulation of hunger and satiation), enhancement of lipolysis and energy expenditure, positive affection of body composition due to improvement of peripheral insulin sensitivity, ultimately favoring lean over fat mass building [ 78 ]. Nevertheless, a recently published randomized, double-blind, placebo-controlled, crossover pilot study (13 patients randomized; 10 concluded) did not find any relevant changes in body weight between the OT arm 16–24 IU at the three main mealtimes and placebo after 8 weeks of treatment [ 79 ]. This finding lays the basis for better-designed multicentric trials to assess the role of OT treatment (alone or in combination) in patients with hypothalamic injuries/dysfunction.…”
Section: Oxytocin and Eating Behaviors: What Do We Know?mentioning
confidence: 99%
“…These positive results could be attributable to the numerous metabolic effects of the neurohormone, including direct reduction of food intake by decreasing appetite in homeostatic and reward-driven conditions (hence, properly insisting on hypothalamic regions involved in the regulation of hunger and satiation), enhancement of lipolysis and energy expenditure, positive affection of body composition due to improvement of peripheral insulin sensitivity, ultimately favoring lean over fat mass building [ 78 ]. Nevertheless, a recently published randomized, double-blind, placebo-controlled, crossover pilot study (13 patients randomized; 10 concluded) did not find any relevant changes in body weight between the OT arm 16–24 IU at the three main mealtimes and placebo after 8 weeks of treatment [ 79 ]. This finding lays the basis for better-designed multicentric trials to assess the role of OT treatment (alone or in combination) in patients with hypothalamic injuries/dysfunction.…”
Section: Oxytocin and Eating Behaviors: What Do We Know?mentioning
confidence: 99%
“…Since OXT also acts outside the hypothalamus, particularly in the brainstem, pharmacological replacement of OXT has been proposed to address features of HO, in particular hyperphagia, as well as some of the psychosocial features of hypothalamic syndrome. In a pilot randomized, placebo‐controlled, crossover study of intranasal OXT (NCT02849743), no significant change in body weight was detected after 8 weeks of OXT, although a modest benefit for anxiety and impulsivity was found 115 . Multiple experimental considerations, including choice of OXT formulation, route of delivery, and technique for OXT measurement in relevant tissues add complexity to the study of this potential treatment.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…In a pilot randomized, placebo-controlled, crossover study of intranasal OXT (NCT02849743), no significant change in body weight was detected after 8 weeks of OXT, although a modest benefit for anxiety and impulsivity was found. 115 Multiple experimental considerations, including choice of OXT formulation, route of delivery, and technique for OXT measurement in relevant tissues add complexity to the study of this potential treatment.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…In this small pilot study with 10 completers, there was no significant effect of intranasal OXT on body weight change. However, OXT was well tolerated, and in exploratory analyses, benefits of OXT for anxiety and impulsivity were noted ( 79 ). Preclinical research using labeled OXT administered intranasally to rhesus macaques or rabbits reached the cerebrospinal fluid and brain ( 80 , 81 ).…”
Section: Recent Drug Discoveriesmentioning
confidence: 99%